ANALISIS GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KEADILAN ORGANISASI TERHADAP KINERJA KARYAWAN DIMEDIASI OLEH KETERIKATAN KARYAWAN - M. Tasnim; Yulihasri Yulihasri (Menara Ilmu, 2020)
This research was conducted aiming to find out the analysis of transformational leadership style and organizational justice towards employee performance mediated by employee engagement, studies on Kawana Padang hotel employees. The independent variables in this study include transformational leadership style, organizational justice. while employee performance is used as the dependent variable, and employee engagement as a mediating variable. The sampling technique is done by sampling saturated which makes the entire population as a sample obtained by 50 employees. The data analysis technique used in this study is logistic regression, where the results obtained are transformational leadership style, organizational justice, and employee engagement significantly and positively influencing employee performance. Keywords : transformational leadership, organizational justice, employee engagement, employee performance